Mössbauer spectroscopy and neutron scattering: Complementary tools for the investigation of magnetic nanostructured systems - Deriu, Antonio (2005)
By a combined use of Mössbauer spectroscopy and polarised small angle neutron scattering, we investigated the structure and magnetic properties of iron nanoparticles obtained by inert gas condensation techniques. The detailed local information on the intrinsic magnetic properties derived from the Mössbauer data have been used in order to build up an appropriate model for the analysis of the magnetic SANS patterns; particle size distributions and magnetisation profiles have thus been deduced.